Opinion spreading and evolution in complex social networks: a simulation study - Wu, Yujie (Nanyang Technological University, 2024)
In an era marked by the growing impact of social media and the complexity of public opinion, research into social opinion evolution has become increasingly important. This dissertation provides a thorough examination of this field, proposing a new model that builds on existing classical frameworks. This model shows potential for revealing important insights into the development of public opinion dynamics within social networks, especially in the complexities of the current digital age.